Valuable interaction with cognitive remediation and optimal antipsychotics for recovery in schizophrenia (VICTORY-S): study protocol for an interventional, open-label, randomized comparison of combined treatment with cognitive remediation and lurasidone or paliperidone - Kubota, Ryotaro; Ikezawa, Satoru; Oi, Hideki; Oba, Mari S; Izumi, Shoki; Tsuno, Ryoko; Adachi, Leona; Miwa, Mako; Toya, Shunji; Nishizato, Yohei; Haga, Daisuke; Iwane, Tatsuro; et al. (Frontiers in Psychiatry, 2024)
There is great interest in improving cognitive function in patients with schizophrenia, as it is critical for adequate social function. Unfortunately, the effect on cognitive function of either pharmacological therapy or psychosocial therapy alone is inadequate. It has been suggested that a combination of these treatments may result in a greater treatment effect. In current clinical practice, some clinicians treat patients with a combination of antipsychotics and cognitive remediation.However, there have been few studies to formally evaluate the effectiveness of this treatment strategy. To date, there has not been a study comparing the combined effect of an antipsychotic, such 2 as lurasidone (demonstrated to improve cognitive function), plus cognitive remediation with the combined effect of another antipsychotic drug plus cognitive remediation. This study addresses that gap and is expected to provide important treatment information to clinicians who treat patients with schizophrenia, aiding in clinical decision-making.